2016
DOI: 10.2494/photopolymer.29.357
|View full text |Cite
|
Sign up to set email alerts
|

Electron Injection from a CdS Quantum Dot to a TiO<sub>2</sub> Conduction Band as an Efficiency Limiting Process: Comparison of QD Depositions between SILAR and Linker Assisted Attachment

Abstract: Sensitization of TiO 2 by semiconductor quantum dots (QDs) initiates a primary charge separation in semiconductor quantum dot sensitized solar cells (QDSSCs), and thus is a key fundamental process controlling their solar cell performance. However, despite extensive researches on QD deposition methods, correlation between the solar cell performance and charge transfer dynamics modulated by the different deposition method has rarely been studied. Here, we demonstrate influence of a CdS QD deposition method on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…[18] Extensive studies have been performed to investigate interfacial charge transfer processes, in particular EI [19,20] and ICR [21] between a QD and TiO2 using transient absorption spectroscopy (TAS). The dynamics results confirm that the EI occurs on ultrafast time scales (typically on subpicosecond to 100 ps), [20,[22][23][24][25] while ICR occurs on nanosecond to microsecond time scale. [23,26,27] However, despite these ample kinetic results and investigation to control the interfacial charge transfer reactions, no study has so far been conducted to correlate the interfacial charge transfer dynamics with the solar cell performance.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…[18] Extensive studies have been performed to investigate interfacial charge transfer processes, in particular EI [19,20] and ICR [21] between a QD and TiO2 using transient absorption spectroscopy (TAS). The dynamics results confirm that the EI occurs on ultrafast time scales (typically on subpicosecond to 100 ps), [20,[22][23][24][25] while ICR occurs on nanosecond to microsecond time scale. [23,26,27] However, despite these ample kinetic results and investigation to control the interfacial charge transfer reactions, no study has so far been conducted to correlate the interfacial charge transfer dynamics with the solar cell performance.…”
Section: Introductionsupporting
confidence: 60%
“…The dynamics results confirm that the EI occurs on ultrafast time scales (typically on subpicosecond to 100 ps), [20,[22][23][24][25] while ICR occurs on nanosecond to microsecond time scale. [23,26,27] However, despite these ample kinetic results and investigation to control the interfacial charge transfer reactions, no study has so far been conducted to correlate the interfacial charge transfer dynamics with the solar cell performance. Therefore, no study was reported to design interfacial structures to optimize QD size and solar cell performance.…”
Section: Introductionsupporting
confidence: 60%
“…Quantum dots are the major absorbers of sunlight and excitons are produced after absorbing light using QDs. Photocurrent is formed by the transfer of electrons to the TiO 2 anode [18]. Based on the previously described relationships, we simulated the solar cells with different sensitizers.…”
Section: Simulation Of the Effect Of Quantum Dot Type On Absorption A...mentioning
confidence: 99%